2010
DOI: 10.1007/s00415-010-5794-y
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal autonomic cephalalgia sine headache

Abstract: Cluster headache without headache (CH-H) has been described several times. We add three new CH-H patients and a patient with (probable) paroxysmal hemicrania without headache (PH-H). We searched the literature and found some more cases of CH-H and PH-H. CH-H attacks may have a shorter minimal attack duration than CH attacks. We propose the term trigeminal autonomic cephalalgia without headache (TAC-H) for autonomic attacks and/or extracephalic pain or sensory symptoms with an attack duration and distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Most recently, Haane et al [20] proposed the term trigeminal autonomic cephalalgia without headache (TAC-H) for autonomic attacks and/or extracephalic pain or sensory symptoms with an attack duration and distribution and/or response to therapy suggesting one of the trigeminal autonomic cephalalgias, but without accompanying headache. In our study, six patients with unclassifiable headaches according to ICHD-II [7] showed complete response to indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Haane et al [20] proposed the term trigeminal autonomic cephalalgia without headache (TAC-H) for autonomic attacks and/or extracephalic pain or sensory symptoms with an attack duration and distribution and/or response to therapy suggesting one of the trigeminal autonomic cephalalgias, but without accompanying headache. In our study, six patients with unclassifiable headaches according to ICHD-II [7] showed complete response to indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, sensory TCC neurons are modulated by the hypothalamus through the neurotransmitters of the orexinergic system, such as orexin A and B (Holland and Goadsby, 2007). Posterior hypothalamus also modulates parasympathetic and sympathetic system via connections with SSN and secondorder sympathetic neurons in the C8-Th2 intermediolateral columns, respectively (Amonoo-Kuofi, 1999; Haane et al, 2011). Dysfunction in these modulatory pathways is currently thought to produce a permissive state for the occurrence of a TAC attack.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Comparées aux crises douloureuses, les crises sont plus brèves (moins de 15 minutes) et moins fréquentes [30]. Ces crises peuvent être isolées ou associées à des crises douloureuses [29,31,32].…”
Section: Connaître Les Formes Cliniques De L'algie Vasculaire De La Funclassified